GAMBARAN PERILAKU IBU YANG MENIKAH DI USIA DINI DALAM PEMENUHAN GIZI BALITA DI DESA PULAU MUNGKUR KECAMATAN GUNUNG TOAR KABUPATEN KUANTAN SINGINGI PROVINSI RIAU TAHUN 2012 - Maya Kaswari; Jumirah .; Muhammad Arifin Siregar (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2013)
A mother who has get married early can be difficult to understand the nutrition problem especially to fullfill the nutrition of under five years old. This research studied a behavior early married women in fullfill the nutrition of under five years old at Village of Pulau Mungkur, subdistrict of Gunung Toar, Regency of Kuantan Singingi, Province of Riau in 2012. This research was a descriptive studied by cross sectional design. The population were early married women had under five years old for 45 people and then to be total sampling. The data was collected by interview using questionnaire, food frequency and food recall form. The result of research show that the behavior about the fulfillment of nutrition for under five years old that classified into less good category. Energy and protein consumption of under five years old was medium category. Generally, the under five years old consumes food three time a day. The nutrition status of under five years old be based on the weight for age, height for age and weight for height is classified into normal category. It is necessary to provide the early married woman and under five years old with exstension about food, nutrition and healthy by the posyandu cadre in order to increase the behavior of mother in fullfill the nutrition need of under five years old and the role of extension about crops food in anticipate the vacant land by the departement of agriculture in order to increase food security of family. Keywords : mother behavior, early marriage, under five years old nutrition